Electronic structure studies of Mg0.95Mn0.05Fe2-2xTi2xO4 (0 <= x <= 0.8) - Kumar, Shalendra; Kumar, Ravi; Thakur, P.; Chae, K. H.; Sharma, S. K. (ELSEVIER, 2008)
The electronic structure of Mg0.95Mn0.05Fe2-2xTi2xO4 (0 <= x <= 0.8) compound is investigated using near edge X-ray absorption. ne structure, (NEXAFS) spectroscopy measurements, carried out at O K, Fe and Ti L-3,L-2-edges at room temperature. The O K-edge spectra indicate that the Fe 3d orbitals have been considerably modified and a new spectral feature start dominating in the pre-edge region at higher Ti doping. The Fe 2p NEXAFS spectra exhibit a mixed valent Fe2+/Fe3+ states apart from the conversion of Fe3+ to Fe2+ with the substitution of Ti ions. The Ti L-3,L-2-edge spectra indicate that Ti ions remain unchanged at 4+ state. These variations in the host electronic structure due to Ti substitution are consistent with the dielectric and transport properties of the material. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: X-RAY-ABSORPTION; MAGNETIZATION; ORIENTATION; FERRITE; EDGES